Gas Consumption and Growth Rate of Hydrogenomonas eutropha in Continuous Culture - Ammann, Elizabeth C. B. (1968)
The bacterium Hydrogenomonas eutropha is under consideration for use in a regenerative life-support system for manned space missions of long duration. A 4-liter continuous culture unit containing the organism was operated for a period of 272 days under autotrophic environmental conditions. The best steady-state run achieved with this unit was observed over a 22-day time interval after 181 days of operation. During this time, the culture consumed an average of 22.9 ± 2.0 ml of carbon dioxide per min, 38.1 ± 3.3 ml of oxygen per min, and 128.5 ± 10.6 ml of hydrogen per min. It required 18.7 ± 1.2 liters of fresh nutrient medium per 24 hr to maintain a constant, preestablished cell population of 1.65 g (dry weight) per liter. The ratio of consumption of carbon dioxide, oxygen, and hydrogen varied from 1:1.2:4.5 to 1:1.9:6.6, with an average of 1:1.7:5.7. Based on these values, approximately 60 liters of the culture would be necessary to balance the gas exchange of one man.